ANALISIS KELAYAKAN USAHATANI PERKEBUNAN KELAPA SAWIT RAKYAT DI DESA RUNTU KECAMATAN ARUT SELATAN KABUPATEN KOTAWARINGIN BARAT - Djoni Djoni (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2018)
The objectives of this study were (1) to analyze the cost components and the cost amount in smallholder oil palm plantations in Runtu Village, Arut Selatan Subdistrict, Kotawaringin Barat Regency (2) to find out the income from the smallholder oil palm plantations in Runtu Village, Arut Selatan Subdistrict, Kotawaringin Barat Regency, (3) to assess the feasibility of the smallholder oil palm plantations in Runtu Village, Arut Selatan Subdistrict, Kotawaringin Barat Regency. The results showed that the calculation of Net Present Value was Rp 20,240,571 ; the Net B/C ratio calculation indicated the number of 1.73 ; the Internal Rate of Return was 21.47% ; the Pay Back Period was 3.5 The value of Pay Back Period indicated that these plantations would have an initial capital payback within 3.5 years since harvesting time or the plant aged 7.5 years old.